Upaya Penyehatan Lingkungan di Jabal Diamond Horse Riding Banjarbaru - Lenie Marlinae; Nita Pujianti; Ayu Riana Sari.Azwari; Muhammad Saidi Hidayat; Yasmine Puspita Sari (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2022)
Abstract Community service is one of the Tridharma of Higher Education as an effort to implement academic knowledge to the community. This year, one of the PSKM FK ULM community service teams in collaboration with the Banjarbaru Food, Agriculture and Fisheries Security Service (DKP3), and Cempaka Agricultural Extension UPT participated in implementing the Tridharma of Higher Education through the 2021 Community Partnership Program. The provision of education carrying the theme of environmental health as an effort to environmental conditions are clean, healthy, comfortable and safe and avoid being disturbed by various diseases has been carried out at Jabal Diamond Horse Riding Banjarbaru in early September 2021. The material presented was about the importance of environmental health, processing organic fertilizers, animal health, and promotion of family medicinal plants with natural fertilizers. All of these materials are made relevant to the output targets to move workers at the farm to process and sell organic fertilizer from horse manure on a regular basis at the farm and to cultivate verticulture of vegetable crops and family medicinal plants using fertilizer from horse manure that has been previously produced. The implementation of the program is published through local print media, Kalimantan Post along with processing the publication in service journals and reference books for optimizing the use of livestock waste into environmentally friendly fertilizer.Keywords: environmental health, horse, organic fertilizer, family medicinal plants (TOGA) AbstrakPengabdian masyarakat merupakan salah satu Tridharma Perguruan Tinggi sebagai upaya implementasi keilmuan akademisi kepada masyarakat. Tahun ini salah satu tim pengabdian masyarakat PSKM FK ULM bekerja sama dengan Dinas Ketahanan Pangan, Pertanian dan Perikanan (DKP3) Banjarbaru serta UPT Penyuluh Pertanian Cempaka turut melaksanakan Tridharma Perguruan Tinggi melalui Program Kemitraan Masyarakat 2021. Pemberian edukasi dengan tema penyehatan lingkungan sebagai salah satu upaya agar kondisi lingkungan bersih, sehat, nyaman dan aman serta terhindar dari gangguan berbagai macam penyakit telah dilaksanakan di sebuah peternakan kuda bernama Jabal Diamond Horse Riding Banjarbaru pada awal September 2021. Materi yang disampaikan mengenai pentingnya kesehatan lingkungan, pengolahan pupuk organik, kesehatan hewan, dan penggalakan tanaman obat keluarga dengan pupuk alami. Seluruh materi dibuat relevan dengan target luaran sehingga diharapkan dapat menggerakkan para pekerja di peternakan untuk mengolah dan menjual pupuk organik dari kotoran kuda di tempat peternakan tersebut secara berkala serta membudidayakan vertikultur tanaman sayur dan tanaman obat keluarga menggunakan pupuk kotoran kuda yang telah diproduksi sebelumnya. Pelaksanaan program dipublikasikan melalui media cetak lokal, Kalimantan Post seiring dengan proses publikasi di jurnal pengabdian dan buku referensi optimalisasi pemanfaatan limbah hewan ternak menjadi pupuk ramah lingkungan.Kata kunci:  kesehatan lingkungan, kuda, pupuk organik, tanaman obat keluarga (TOGA)